Salicylate pharmacokinetics in patients with rheumatoid arthritis. - Owen, S G (1989)
1. The pharmacokinetics of salicylic acid (SA) and its major metabolite salicyluric acid (SU) were studied in nine patients with rheumatoid arthritis following a 900 mg oral dose of acetylsalicylic acid and during 6 weeks of chronic administration of enteric coated aspirin (3,900 mg day). Response to therapy was also monitored. 2. The various pharmacokinetic parameters determined in the study were similar to those observed in other single dose salicylate studies amongst healthy volunteers but were not predictive of salicylate concentration in the chronic dose study. 3. Plasma concentrations of SA (total and unbound) were found to decline significantly over the 6 weeks and plasma SU concentrations increased. 4. During the chronic dosing study, there was a significant increase in the Vmax (total and unbound) for the formation of SU, whilst the Km and SU clearance remained constant. Also, the elimination rate constant (k) for salicylate was not significantly affected. 5. Therapeutic response to salicylate therapy was not significantly affected by the decline in SA concentrations.